New identities and Parseval type relations for the generalized integral transforms L4n, P4n, Fs, Fs,2n and Fc,2n - Dernek, Nese; Olcucu, Eyup Omer; Aylikci, Fatih (ELSEVIER SCIENCE INC, 2015)
In the present paper, the authors consider several new integral transforms including the L-4n-transform, the P-4n-transform, the F-s,F-2n-transform and the F-c,F-2n-transform as generalizations of the classical Laplace transform, the classical Stieltjes transform, the classical Fourier sine transform and the classical Fourier cosine transform, respectively. Identities involving these transforms are given. Using this identities, a number of new Parseval-Goldstein type identities are obtained. Some examples are also given as illustrations of the results presented here. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: Laplace transforms; Widder potential transforms; L-4n-transforms; P-4n-transforms; epsilon(4n,1)-transforms; Parseval-Goldstein type theorems; P-4-TRANSFORM; Mathematics